Analysis of the most frequent nonconformance aspects related to Good Manufacturing Practices (GMP) among small and medium enterprises (SMEs) in the food industry and their main factors - Noor Hasnan, Noor Zafira; Kadir Basha, Roseliza; Mohd Amin, Nor Amaiza; Mohd Ramli, Sharifah Hafiza; Yew, John Huat Tang; Ab Aziz, Norashikin (Elsevier, 2022)
Despite the increasing evidence that small processors have a low rate of food safety compliance, primarily due to the lack of Good Manufacturing Practice (GMP) implementation, only a limited number of research studies have been conducted to understand their challenges. The aims of this review were twofold, namely 1) to analyse the GMP’s most frequent nonconformance aspects in small food processing and (2) to elucidate the key factors that lead to the nonconformance aspects. The review was carried out based on twenty peer-reviewed publications between the years 2012 to 2021, which collected studies related to GMP and small-scale processors. Inadequate sanitary design and facilities were identified as the most frequent GMP nonconformance aspect (85% of the total number of publications), followed by poor personal hygiene (55%), inadequate or absence of documentation (55%), poor cleaning and maintenance programs (50%), lack of operation control (50%), lack of training (35%), inadequate product information (15%) and lack of workers’ health control (15%). Such nonconformances were found to result in incidences of foodborne diseases, unacceptable microbial growth in products and ambient areas, quality degradation as well as findings of filthy matters. The factors that led to nonconformance were the lack of on-site supervision, financial constraints, lack of knowledge, lack of managerial support, the gap in authority's enforcement and workers' resistance to food safety practices. The review concludes with a suggestion for future work to formulate a cohesive program that integrates multiple strategies in addressing the identified key factors and subsequently, enabling GMP adoption among SMEs.